2006
DOI: 10.1177/0145721705284372
|View full text |Cite
|
Sign up to set email alerts
|

Using Focus Groups to Develop a Culturally Competent Diabetes Self-management Program for Mexican Americans

Abstract: Culturally competent diabetes self-management for Latinos should incorporate the family and include techniques for stress management as well as diet modification. Information delivery should include a variety of techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 16 publications
11
83
1
1
Order By: Relevance
“…This finding has been cited in other studies (Brown & Hanis 1999;Rosal et al 2004;Vincent et al 2006). The health professionals also indicated that inclusion of a peer educator would further enhance learning, which is also supported by other studies (Vincent et al 2006).…”
Section: Recommendations For An Ne Programmesupporting
confidence: 81%
See 4 more Smart Citations
“…This finding has been cited in other studies (Brown & Hanis 1999;Rosal et al 2004;Vincent et al 2006). The health professionals also indicated that inclusion of a peer educator would further enhance learning, which is also supported by other studies (Vincent et al 2006).…”
Section: Recommendations For An Ne Programmesupporting
confidence: 81%
“…This finding has been observed in other studies (Brown & Hanis 1999;Vincent et al 2006). A notable finding is the recommendation to include family members in the education, a suggestion also articulated by the health professionals.…”
Section: Recommendations For An Ne Programmesupporting
confidence: 81%
See 3 more Smart Citations